(untitled) - Deming, W. Edwards (Cambridge, 1994)
In this book W. Edwards Deming details the system of transformation that underlies the 14 Points for Management presented in Out of the Crisis. The system of profound knowledge, as it is called, consists of four parts: appreciation for a system, knowledge about variation, theory of knowledge, and psychology. Describing prevailing management style as a prison, Deming shows how a style based on cooperation rather than competition can help people develop joy in work and learning at the same time that it brings about long-term success in the market. Indicative of Deming's philosophy is his advice to abolish performance reviews on the job and grades in school.
Keywords: Condition economis; Education aspects